2000
DOI: 10.1212/wnl.55.6.880
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpes simplex virus type 1 in human vestibular nuclei

Abstract: The distribution of herpes simplex virus type 1 (HSV-1) in human geniculate, vestibular ganglia, and vestibular nuclei was determined in 10 human temporal bones and brainstems of five individuals by PCR. HSV-1 was found in 3 of 10 of each ganglia and vestibular nuclei. The various patterns of HSV-1 infection of vestibular structures are compatible with virus migration from the vestibular ganglia to the vestibular nuclei and from the ipsilateral to the contralateral vestibular nucleus via commissural fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 9 publications
1
26
0
5
Order By: Relevance
“…It is widely accepted that after primary infection (stomatitis herpetica) HSV-1 ascends to associated sensory ganglia by retrograde axonal transport, e.g., via chorda tympani in the GG and via faciovestibular anastomosis to the VG [Bergström, 1973;Whitley, 1988]. A recent study reported the presence of HSV-1 not only in VGs but also in vestibular nuclei, thus indicating that viral migration can also occur via the vestibular nerve to the pontomedullary brainstem [Arbusow et al, 2000] ( fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that after primary infection (stomatitis herpetica) HSV-1 ascends to associated sensory ganglia by retrograde axonal transport, e.g., via chorda tympani in the GG and via faciovestibular anastomosis to the VG [Bergström, 1973;Whitley, 1988]. A recent study reported the presence of HSV-1 not only in VGs but also in vestibular nuclei, thus indicating that viral migration can also occur via the vestibular nerve to the pontomedullary brainstem [Arbusow et al, 2000] ( fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…A viral etiology of VN is supported by studies showing inflammatory degeneration of the vestibular nerves and the presence of herpes simplex virus 1 (HSV-1) DNA as well as latency-associated transcript (LAT) in the vestibular ganglia (VG) (6)(7)(8)(9). After primary infection, usually occurring via the oral mucosa of the mouth, HSV-1 infects the trigeminal ganglion (TG) and can reach the geniculate ganglion (GG) via the lingual nerve.…”
mentioning
confidence: 99%
“…Reactivation can occur during different diseases such as herpes labialis (TG) and, in rarer cases, Bell's palsy (GG), sudden hearing loss, or vestibular neuritis (VG). Such a reactivation of HSV-1 from the VG has been proposed to cause vestibular neuritis, although final confirmation is still lacking (6)(7)(8)10).…”
mentioning
confidence: 99%
“…The many terms -vestibular neuritis / neuronitis / neuropathy / neuronopathy, acute vestibulopathy, acute vestibular neurolabyrinthitis, acute labyrinthitis 1 -often used interchangeably to describe PVP, testify to the fact that there is still much to be discovered about the nature of the disease.A less disputed issue is the fact that PVP is often preceded by a viral infection of the upper respiratory tract [37] or the higher prevalence (compared to controls) of Herpes viruses in the eighth and other cranial nerves and their neurons [1,12,17,41] as well as in the saliva of patients with PVP [33]. One animal study also supports the etiopathogenetic role of Herpes viruses, but points to histopathological changes in both the vestibular nerve and labyrinth [13].…”
Section: Etiology and Pathogenesis Of Pvp: The Evidence So Farmentioning
confidence: 97%